PENGUATAN PERAN PEREMPUAN DALAM PENGELOLAAN HARTA PUSAKA TINGGI DI MINANGKABAU - Yuhelna Yuhelna; Sri Rahmadani; Waza Karia Akbar (Ekasakti Jurnal Penelitian dan Pengabdian, 2021)
The problem of managing inheritance in West Sumatra, especially in Minangkabau, is getting more and more difficult to resolve through deliberation to reach a consensus. This can be seen from the increasing number of cases of inheritance disputes in court. It cannot be denied that one of the causes is the weakening or decreasing role or involvement of women in the management of inheritance which is traditionally "assigned" to Minangkabau women. The decline in women's participation in the management of inheritance in Minangkabau is inseparable from the lack of knowledge of Minangkabau women in this era of globalization regarding the status of “Minang women”. The era of globalization is said to have had a big influence on the mindset of Minang women on their status and role. Therefore, it is necessary to increase knowledge about the role of Minangkabau women in the management of inheritance so that then it will lead to women who have the capacity to manage these heritage assets. In the end, by strengthening the role of women in the management of inheritance, it can minimize the conflict problems that can occur.